La expresión de la idea de “problema” en el latín de Plauto. Análisis de Semántica Cognitiva - García Jurado, Francisco (Cuadernos de Filología Clásica. Estudios Latinos, 2004)
What is a problem in Latín? How do we express this concept? We have not found any specific word to express what is aproblem ¡n the LatinofPlautus. In contrast, this Latin makes use of several words and expresions that reflect our experience of a problem as a thing that falls on us, a place without exit, a thing that does not move, an obstacle in our way, or a knot. The aim of this paper is to consider what is a problem in Latín from a cognitive perspective. We shall study etymologies of latin words for “problem’ and “solution” and usual expressions such as haeret haec res, or vadum salutis, where it is possible to find Source Domains (places, exits...) by which Abstract Concepts can be established as Target Domains to express the complex concept of problem, according to spatial and ontological metaphors.
Keywords: Cognitive Sernanties; Latín Language; Problem; Plautus